Peningkatan Kewirausahaan Dan Kemandirian Ekonomi Pada UMKM Mebel Melalui Penerapan Pemasaran Digital - Mu'tasim Billah; Achmad Rafinsyah; Adira Mawangga Putri; Ayu Oktavianingrum; If’idatur Rosyidah (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
KKN MBKM Thematic is a community service activity formed by universities. This activity was carried out by students with the theme of entrepreneurship in Nglebak Village. The aim of this project is to provide wider opportunities for communities to develop their businesses in a more contemporary, efficient and inclusive manner. In addition, this project aims to increase students' knowledge and integrate it into the environment. This is to identify and solve problems faced by the 06 KKN-T MBKM group, such as creating digital marketing through Instagram social media which contains content about furniture products in an attractive appearance so that they are more easily recognized in the eyes of the wider community. To realize the development of the furniture business in this community service activity, group 06 KKN-T MBKM carried it out using detailed and gradual implementation methods starting from surveys, observations, and Focus Group Discussions (FGD). The steps taken to help digital marketing for MSMEs Furniture are starting with creating a business name, creating a product logo, creating an e-commerce account, and creating a social media account.